Key points to read Mo Yan - Chaohui, Chen (Sinología hispánica. China Studies Review, 2021)
Mo Yan, the winner of the Nobel Prize in Literature in 2012, is unquestionable one of the most famous Chinese contemporary writers in the world. The present work tries to finish a complete investigation to the biography and the literary works of Mo Yan and aims to extract five most important key points of his works —the hunger, the ghosts, the mother, the nostalgia and the critics to the officials— to offer a precise and profound understanding to the literary and social value Mo Yan’s artistic production.